Analisis Perlindungan Hukum Pemegang Hak Desain Industri Terdaftar di Indonesia - Rissa Afni Martinouva (KEADILAN PROGRESIF, 2018)
Law Number 31 of 2000 concerning the Right of Industrial Design gives the Right to the Designer both individually and together with several other people who produce creations about form, configuration, or composition of lines or colors, or lines and colors, or a combination thereof in the form three dimensions or two dimensions that give an aesthetic impression and can be realized in three-dimensional or two-dimensional patterns and can be used to produce a product, item, industrial commodity, or handicraft. Furthermore, the results of the creation are called Industrial Designs. The Act has also regulated and provided an understanding of the subject of industrial design, objects of industrial design rights, legal principles of industrial design rights, acquisition of industrial design rights and also regulates legal protection of industrial design rights holders through criminal sanctions against those who violate them. There are violations of industrial design rights in Indonesia, thus making the laws governing them increasingly play a role supported by complex solutions and providing maximum efforts to protect the problems of industrial design rights. This study discusses the regulatory system of industrial design rights, the form of violations and legal protection efforts for industrial design rights holders who have registered according to Law No. 31 of 2000 concerning Industrial Design.